2016
DOI: 10.1016/j.rbmo.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone/chorionic gonadotrophin receptor overexpressed in granulosa cells from polycystic ovary syndrome ovaries is functionally active

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractPolycystic ovarian syndrome (PCOS) is associated with anovulatory infertility. Luteinizing hormone/chorionic gonadotropin receptor (LHCGR), which is critical for ovulation, has been suggested to be expressed prematurely in the ovarian follicles of women with PCOS. The objective of this study was to analyse the expression and activity of LHCGR in ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…One previous study in GCs from hSAFs found a significantly higher expression of LHCGR in PCOS, and, interestingly, this was a feature of most follicles analyzed in that study (15). We also demonstrated a higher LHCGR expression in GCs from PCO hSAFs and PCOS GLCs, as has been shown previously (43, 44).…”
Section: Discussionsupporting
confidence: 90%
“…One previous study in GCs from hSAFs found a significantly higher expression of LHCGR in PCOS, and, interestingly, this was a feature of most follicles analyzed in that study (15). We also demonstrated a higher LHCGR expression in GCs from PCO hSAFs and PCOS GLCs, as has been shown previously (43, 44).…”
Section: Discussionsupporting
confidence: 90%
“…Recent genome-wide association cohort studies (GWAS) into PCOS discovered new susceptibility loci associated with 17 genes [reviewed by [15]]: DENN domaincontaining 1A (DENND1A), luteinising hormone/chorionic gonadotrophin receptor (LHCGR), follicle stimulating hormone beta subunit (FSHB), follicle stimulating hormone receptor (FSHR), yes associated protein 1 (YAP1), insulin receptor (INSR), ras-related protein RAB5B, TOX high mobility group box family member 3 (TOX3), high mobility group AThook 2 (HMGA2), chromosome 9 open reading frame 3 (C9orf3), GATA binding protein 4 (GATA4), Erb-B2 receptor tyrosine kinase 4 (ERBB4), DNA repair protein (RAD50), thyroid adenoma associated (THADA), sulphite oxidase (SUOX), Ca2+/calmodulin-dependent protein kinase (KRR1) and the small ubiquitin-like modifier 1 pseudogene 1 (SUMO1P1) [16][17][18][19]. Many human studies have been conducted in an effort to investigate these PCOS candidate genes, particularly DENND1A and its variants [20], TOX3 [21], FSHR [22], LHCGR [23] and INSR [24]. Another PCOS susceptibility loci was identified earlier by case-cohort studies using microsatellite analyses and it is located in an intron of fibrillin 3 (FBN3) [25].…”
Section: Introductionmentioning
confidence: 99%
“…While the etiopathogenesis of PCOS remains elusive, it likely involves aberrant hormonal responses mediated by ovarian granulosa cells (GCs) during the progression of follicular development. Previous studies have reported that PCOS is associated with elevated luteinizing hormone (LH) and overexpression and overactivation of the luteinizing hormone/chorionic gonadotropin receptor (LHCGR) in GCs from PCOS patients and that this prevents follicle maturation and ovulation 12 16 . Impaired GC function is associated with disruption of folliculogenesis and with elevated intraovarian androgens and circulating anti-Müllerian hormone levels 17 – 23 .…”
Section: Introductionmentioning
confidence: 99%